GIDROIZOMERIZACIYA PROCESI – ZAMANAGÓY, EKOLOGIYALÍQ TAZA BENZIN FRAKCIYALAR ALÍWDÍŃ TIYKARǴÍ USÍLÍ SÍPATÍNDA - Svaykosov, S.O.; Turdimuratov, P.; Maxmudov, M.J. (SCIENCE and SOCIETY, 2025)
The article presents scientific and technical data on the hydroisomerization of gasoline fractions in which benzene accumulates as a way to obtain environmentally friendly and high-octane components of motor fuel. Data on the advantages and disadvantages of the main methods of catalytic processing of benzene-containing fractions are presented on the hydrogenation of benzene, alkylation of benzene with olefins, and prospects for the hydroisomerization of benzene-containing fractions.